THE TARAPORE COMMITTEE'S RECOMMENDATIONS FOR CAPITAL ACCOUNT CONVERTIBILITY AND LIBERALIZATION IN INDIA - Cullinane, K. B; Mason, K. J (Economics and Statistics Research Journal (ESRJ), 2022)
The COVID-19 pandemic had far-reaching social, political, and economic impacts globally. The United States was hit especially hard by the pandemic, with over 34 million cases and over 609,000 deaths by July 2021. The pandemic also had a significant impact on the political landscape, as authorities implemented control and mitigation measures. In Texas, a traditionally Republicanmajority state, the pandemic led to key changes in political campaigning strategies. Republican candidates modified their campaign tactics to adapt to the new environment. Using interviews with Texas Republican campaign managers and consultants during the 2020 general election, this case study examines the impact of COVID-19 on political campaigns in Texas. The study also draws comparisons with Democratic Party campaigns during the same period, providing insights into the effectiveness of face-to-face campaigning and different approaches to campaign decision making. The case study highlights the potential benefits of engaging in a bottom-up campaign strategy during uncertain election environments, emphasizing the importance of campaign adaptations during crises. The findings provide valuable insights into what happened during the election and can inform future political campaign strategies during pandemics